A study of treatment compliance of dog bite cases reporting to anti-rabies clinic of M.K.C.G Medical College, Odisha, India - Jena, Dhaneswari; Tripathy, R. M.; Pradhan, Srabani; Mahapatra, Dillip Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Rabies a dreadful disease can easily be prevented by immediate wound care, vaccination and immunoglobin administration. Prognosis depends on the promptness of initiation, regularity and completion of treatment, determined by patient’s compliance. It partly depends on the patience and devotion of doctor for counselling the patient. The objectives of the study were to assess the treatment compliance of dog bite cases attending tertiary care centre for post exposure prophylaxis (PEP) of Rabies. Methods: It is a record based longitudinal study, conducted in Anti- Rabies Clinic of M.K.C.G Medical College from January 2016 to July 2016. Patients registered on first visit followed up to the 4th dose, the last cases registered on June 15th was followed up to July31st to declare it as completed, delayed or defaulted as decided. Results: Total 1658 cases were registered during the study period. Most of them were male (73.8%) and ≤20 yrs of age. 1222 cases (73.7%) completed treatment, out of which 793 cases completed on schedule and 429 cases delayed the doses. 436 (26.3%) cases had defaulted treatment i.e. missed one or more dose. Significant associations were found between treatment completion status and place of residence, education and age of the participants. Reporting within 1 day of the bite is associated with better compliance to PEP, showing their good health seeking behaviour. Completion rate was significantly higher in category III cases. Conclusions: Intensive counselling needs to be done on day 1 and day 7th day of vaccination.